2020
DOI: 10.3390/jof7010011
|View full text |Cite
|
Sign up to set email alerts
|

Botrytis cinerea Transcriptome during the Infection Process of the Bryophyte Physcomitrium patens and Angiosperms

Abstract: Botrytis cinerea is a necrotrophic pathogen that causes grey mold in many plant species, including crops and model plants of angiosperms. B. cinerea also infects and colonizes the bryophyte Physcomitrium patens (previously Physcomitrella patens), which perceives the pathogen and activates defense mechanisms. However, these defenses are not sufficient to stop fungal invasion, leading finally to plant decay. To gain more insights into B. cinerea infection and virulence strategies displayed during moss colonizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 106 publications
(155 reference statements)
2
16
0
Order By: Relevance
“…This reprograming of host cell response has been also described in liverwort and hornwort during colonization by symbiotic fungi [ 31 , 32 ]. Moreover, the cell death process triggered as part of the HR response, evidenced by the cytoplasmic collapse and chloroplast browning, indicates that P. patens attempted to control C. gloeosporioides infection, as was previously reported [ 23 ]. HR is triggered during association with pathogens; it plays an important role in restricting pathogen growth and also regulates the local and distant tissues defense responses [ 33 ].…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…This reprograming of host cell response has been also described in liverwort and hornwort during colonization by symbiotic fungi [ 31 , 32 ]. Moreover, the cell death process triggered as part of the HR response, evidenced by the cytoplasmic collapse and chloroplast browning, indicates that P. patens attempted to control C. gloeosporioides infection, as was previously reported [ 23 ]. HR is triggered during association with pathogens; it plays an important role in restricting pathogen growth and also regulates the local and distant tissues defense responses [ 33 ].…”
Section: Resultssupporting
confidence: 62%
“…Because C. gloeosporioides directly penetrates the host cell walls, their molecular composition is extensively modified and strengthened by lignification in flowering plants or accumulation of callose and phenolic compounds in non-vascular plants [ 30 ]. The positive staining with safranin-O on cells from 8 hai onward demonstrated that lignan-like compounds are accumulated in P. patens cells to reinforce its cell walls as a defense mechanism against fungal infection [ 22 , 23 , 24 ]. Consistent with our results, infection with other pathogens, such as the hemibiotrophic oomycete Phytophthora capsici and the necrotrophic fungus B. cinerea , provoke browning of chloroplasts and its migration towards the active infection site and cytoplasmatic shrinkage [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, transcriptome sequencing was used to analyze the gene expression of S. sclerotiorum treated with the fermentation broth of Bacillus amyloliquefaciens [28]. Transcriptomic analysis was also conducted to analyze critical genes involved in the infection process of B. cinerea [58], as well as the resistance-related genes of the B. cinerea B05.10 strain in response to fungicide cyprodinil and fenhexamid [57]. In this research, we showed the effective inhibitory effect of ε-PL on S. sclerotina, as well as on B. cinerea, and compared the effects of ε-PL between two typical necrotrophic patho-genic fungi by revealing regulatory trends on the critical genes and pathways of the pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…The grey mould caused by Botrytis cinerea damages many crop hosts (over 200 species) worldwide [2,3]. This fungus mainly enters the plant via direct penetration or natural openings or wounds [4,5]. B. cinerea is also a significant threat to greenhouse-grown plants, where disease control is usually challenging and expensive [6].…”
Section: Introductionmentioning
confidence: 99%